Detection of pathogenic Leptospira species associated with phyllostomid bats (Mammalia: Chiroptera) from Veracruz, Mexico. Issue 3 (10th January 2018) - Ballados‐González, G. G.; Sánchez‐Montes, S.; Romero‐Salas, D.; Colunga Salas, P.; Gutiérrez‐Molina, R.; León‐Paniagua, L.; Becker, I.; Méndez‐Ojeda, M. L.; Barrientos‐Salcedo, C.; Serna‐Lagunes, R.; Cruz‐Romero, A.
Summary: The genus Leptospira encompass 22 species of spirochaetes, with ten pathogenic species that have been recorded in more than 160 mammals worldwide. In the last two decades, the numbers of records of these agents associated with bats have increased exponentially, particularly in America. Although order Chiroptera represents the second most diverse order of mammals in Mexico, and leptospirosis represents a human and veterinary problem in the country, few studies have been conducted to identify potential wildlife reservoirs. The aim of this study was to detect the presence and diversity of Leptospira sp. in communities of bats in an endemic state of leptospirosis in Mexico. During January to September 2016, 81 bats of ten species from three localities of Veracruz, Mexico, were collected with mist nets. Kidney samples were obtained from all specimens. For the detection of Leptospira sp., we amplified several genes using specific primers. Amplicons of the expected size were submitted to sequencing, and sequences recovered were compared with those of reference deposited in GenBank using the BLAST tool. To identify their phylogenetic position, we realized a reconstruction using maximum‐likelihood (ML) method. Twenty‐five samples from three bat species ( Artibeus lituratus, Choeroniscus godmani and Desmodus rotundus ) showed the presence of Leptospira DNA. Sequences recovered were close to Leptospira noguchii, Leptospira weilii and Leptospira interrogans . Our results include the first record of Leptospira in bats from Mexico and exhibit a high diversity of these pathogens circulating in the state. Due to the finding of a large number of positive wild animals, it is necessary to implement a surveillance system in populations of the positive bats as well as in related species, in order to understand their role as carriers of this bacterial genus.